Analysis Of Life Index (Li) Indicators Of Young People Of Military Age In Different Local Regions Of The Republic Of Karakalpagistan - Rzaev Raxat Muratbaevich; Khalmuratova Jumagul Mafurovna (Periodica Journal, 2024)
The comparative characteristics of anthropometric and morphofunctional parameters of teenagers of military conscription age in different regions of Karakalpakstan were studied
Keywords: indicators; Karakalpakstan; characteristics; morphofunctional